Implementation Of Object-Oriented Programming With Pyqt: Development Of Calculation Application - Elan Maulani, Isma; Azis, Irfan; Cahya, Melani Nur; Komarudin, Komarudin; sagita, Ahmad bahar (Green Publisher Indonesia, 2024)
This practical report discusses the implementation of object-oriented programming using PyQt in developing calculation applications. The discussion includes application development steps, object structure, and responsive user interface integration. The development method used incorporates object-oriented programming concepts to increase modularity and maintainability of the code. The resulting calculation application is able to provide an interactive and efficient user experience. It is hoped that the results of this practicum can be a reference for students of object-oriented programming and application development using PyQt